Regulation of viral RNA-dependent RNA polymerases by phosphorylation - Duflos, Camille; Michiels, Thomas (Frontiers in Virology, 2023)
RNA viruses encode an RNA-dependent RNA polymerase (RdRp), which is essential for transcription and replication of their genome since host cells lack equivalent enzymes. RdRp residues were shown to be phosphorylated by host kinases in several human, animal or plant viruses including flaviviruses, picornaviruses, coronaviruses, influenza viruses and tymoviruses. RdRps can be phosphorylated on several residues by distinct host kinases. Phosphomimetic mutations of identified phosphorylated residues either positively or negatively regulate RNA synthesis or association of RdRps with RNA or other proteins. Interestingly, some RdRps evolved to recruit cellular kinases through direct protein-protein interaction, likely to promote or to tightly control their own phosphorylation. Given the essential nature of RdRps for RNA virus replication, a better knowledge of RdRps’ phosphorylation is expected to facilitate the design of future drugs that strongly affect polymerase activity.